HUBUNGAN AKTIFITAS FISIK DENGAN TINGKAT STRES PADA LANSIA PENDERITA HIPERTENSI - Esa, Fitriani Dewi; Sopiah, Popi; Rosyda, Rafika (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2023)
The number of elderly people in Indonesia is increasing which occurs with increasing age which has an impact on their health, such as physical activity in the elderly which is caused by the aging process and the process of the occurrence of a disease. In line with the high number of elderly people who suffer from hypertension, one of which is caused by a lack of physical activity. Risk factors for hypertension include obesity, salt consumption, alcohol consumption, coffee drinking habits, physical activity, stress, and smoking (Herawati et al., 2020).The purpose of this study was to determine the relationship between physical activity and stress levels in elderly people with hypertension. The research design is a correlational descriptive quantitative study. The survey questionnaire was used by researchers to measure physical activity in elderly hypertensives with the IPAQ questionnaire and to measure stress levels using the DASS-42 questionnaire. The results of the bivariate analysis obtained sig. P = 0.145> 0.005, the data stated that there was no significant relationship between physical activity and stress levels in elderly hypertension.Keywords: physical activity, stress level, elderly, hypertension.